Community-based recovery interventions for improving mental health in schizophrenia patients: a scoping review in Southeast Asia - Rohman Hikmat; Suryani Suryani; Iyus Yosep; Rohani Jeharsae; Efri Widianti; Nur Oktavia Hidayati; Titin Sutini; Taty Hernawaty; Aat Sriati; Imas Rafiyah (BMC Psychiatry)
Abstract Background Schizophrenia is a complex mental health condition that affects an individual’s thoughts, perceptions, emotions, and behavior. Recovery from schizophrenia is not solely defined by symptom reduction, but also by the ability to lead a meaningful and fulfilling life within the community. Recovery-oriented approaches emphasize hope, empowerment, social inclusion, and the rebuilding of identity. In Southeast Asia, community-based interventions play a crucial role in supporting individuals diagnosed with schizophrenia through culturally relevant, accessible, and holistic care. Aim This scoping review aims to explore the types and characteristics of community-based recovery interventions implemented for individuals diagnosed with schizophrenia in Southeast Asia, specifically in Indonesia, Malaysia, and Thailand. Methods A scoping review was conducted following Arksey and O’Malley’s framework. Literature searches were performed in five databases: Scopus, PubMed, CINAHL, Web of Science, and Google Scholar. Keywords included “recovery”, “intervention”, “community-based”, “schizophrenia”, “psychiatric”, and “psychosis”. Inclusion criteria were: (1) studies involving individuals diagnosed with schizophrenia (2), studies conducted in Indonesia, Malaysia, or Thailand (3), articles published in English or Indonesian between 2014 and 2024, and (4) studies focusing on recovery-related outcomes. A qualitative descriptive analysis was used to synthesize findings. Results A total of 10 eligible articles were included. The studies explored a variety of community-based recovery interventions, such as psychoeducation programs, empowerment and self-management training, forgiveness therapy, horticultural therapy, web-based cognitive training, and psychosocial interventions including relaxation techniques and mindfulness-based self-awareness. These interventions were found to enhance patients’ knowledge, coping skills, social functioning, and overall quality of life. Conclusion Community-based recovery interventions in Southeast Asia show promise in supporting individuals with schizophrenia in their recovery journey. These approaches address not only clinical symptoms but also social and psychological well-being. Further research is needed to evaluate the long-term effectiveness, cultural adaptability, and sustainability of such interventions in diverse community settings.